IMPROVEMENT OF SCIENCE LEARNING OUTCOMES THROUGH IMAGE MEDIA IN PRIMARY SCHOOL STUDENTS - Titien Fauziyah (Institut Pendidikan Tapanuli Selatan, 2021)
The research objective is to improve the learning outcomes of science subjects by using the image media method for fifth grade students of SD Negeri 170 / IX Marga. The subjects of the learning improvement activity were grade 4 students of SDN 187 / IX Tanjung Harapan with 25 students consisting of 14 male students and 11 female students. The results of research in the pre-cycle, the average value of student learning outcomes in science is 43.08 and none of the students reached the KKM. Then in the first cycle the students' science learning outcomes on average 1.807 and students who reached the KKM were 9 students (23%). In the second cycle the average value of student learning outcomes reached 82.56 and students who reached KKM 25 students (100%).